2011
DOI: 10.1159/000324577
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus Prevents Short-Term Renal Changes Induced by Ischemia-Reperfusion Injury in Rats

Abstract: Background: Ischemia-reperfusion (I/R) is present at various degrees in kidney transplants. I/R plays a major role in early function and long-term survival of renal allograft. The purpose of our study was to determine if immunosuppressants modulate I/R in a model that separates I/R from all immune responses. Methods: Sprague-Dawley rats with monolateral renal I/R received daily cyclosporine (A), tacrolimus (B), sirolimus (C) or saline (D). Sham-operated rats received saline (E). After 30 days, glomerular filtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 57 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…Its overexpression occurs in experimental and clinical acute tubular injury [44][45] and in models of CsA-induced nephrotoxicity [28][29]. The early increase in the urinary excretion and renal tissue overexpression of fibronectin observed in this study were most likely associated with tubular injury resulting directly from CsA toxicity to renal tubular cells or CsA-induced renal ischemia.…”
Section: Discussionmentioning
confidence: 60%
“…Its overexpression occurs in experimental and clinical acute tubular injury [44][45] and in models of CsA-induced nephrotoxicity [28][29]. The early increase in the urinary excretion and renal tissue overexpression of fibronectin observed in this study were most likely associated with tubular injury resulting directly from CsA toxicity to renal tubular cells or CsA-induced renal ischemia.…”
Section: Discussionmentioning
confidence: 60%
“…Among the methods tested for attenuation of renal IRI are many drugs [22,23], endocrine hormones [24], erythropoietin [21], and small interfering RNA [25]. Various drawbacks, however, have prevented their clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects have been reported in the work of Lieberthal et al [27], who found no differences in kidney function on day 7 after induced IRI between non-treated and rapamycin-treated rats, but by day 6 after induced IRI, rapamycin-treated animals had lower GFR and worse histology score. It is important to note that when renal function was explored 30 days after induced renal IRI in rats, it was found that rapamycin prevented GFR decline [28]. …”
Section: Discussionmentioning
confidence: 99%